Pengaruh Kualitas Pelayanan Transjakarta Terhadap Kepuasan Pengguna - Yudhistira, Keisha (Jurnal Ilmiah Wahana Pendidikan, 2025)
This writing aims to determine the Effect of Transjakarta Service Quality on User Satisficastion as well as to add insight and knowledge related to PT. Transjakarta. The method used in writing this journal is distributing questionnaires to users of Transjakarta Bus services. The result of this study are in terms of services and facilities of PT. Transjakarta has been very goof at providing it, but there is still more that needs to be improved, such as cleanliness and other facilities so that users feel comfortable